Reliability and validity of the International Classification of Functioning，Disability and Health Rehabilitation set in the Rehabilitation of Knee Osteoarthritis - LEI Lei; PENG Zhizhou; GAO Mingyue; LI Fei; MAO Ningning; WU Xi; XIAO Chengcheng; XUN Yajing; ZHAO Suchen; FAN Xiaojun (康复学报)
Objective To discussed the reliability and validity of the "International Classification of Functioning, Disability and Health Rehabilitation Set" （ICF-RS） in assessing the functional status of body function, activity and participation in patients with knee osteoarthritis （KOA）. Methods From October to December, 2022, 60 cases of KOA patients in Bone injury Rehabilitation clinic of the Fifth Hospital of Xiamen and the Hubei Xiangyang central hospital were recruited. Patients’ function were assessed by ICF-RS. The criterion-related validity between the ICF-RS scale and the common clinical scale was analyzed ［Visual Analogue Scale （VAS） Pain Score, Hospital for Special Surgery knee score （HSS） , Modified Barthel Index （MBI）, and the MOS item short from health survey, （SF-36）］, which was in order to evaluate the effectiveness of ICF-RS scale on function and activity performance in patients with KOA. The reliability and validity of the ICF-RS were evaluated by internal consistency and item differentiation. Results （1）The ICF-RS functional status：60% of KOA patients had no or mild functional impairments. The most common moderate to severe impairments in physical functions included b280 pain in 54 cases （90. 00%）, b455 exercise tolerance function in 44 cases （73. 33%）, and b134 sleep function in 28 cases （46. 66%）; the most common moderate to severe impairments in activities included d455 moving around in 52 cases （86. 67%） and d410 changing basic body position in 30 cases （50. 00%）; the most common moderate to severe impairments in participation included d660 helping others in 38 cases （63. 33%）, d850 paid employment in 32 cases （53. 33%）, and d920 recreation and leisure in 38 cases （63. 33%）. （2）criterion-related validity：ICF-RS body function scores were negatively correlated with HSS scores （r>0. 4, P<0. 05）, and ICF-RS physical activity scores were negatively correlated with MBI, HSS, and SF-36 bodily pain dimension scores （r>0. 6, P<0. 05）. ICF-RS participation scores were negatively correlated with MBI and HSS scores （r>0. 6, P<0. 05）. （3）Reliability and validity analysis：The Cronbach α for ICF-RS in KOA patients was 0. 932 （P<0. 05）. The Cronbach α coefficient of the ICF-RS scale was reduced except for deleting b620 urinary function, b730 muscle strength function, d710 basic interpersonal communication, and d850 paid employment. The 70. 00% （21/30） items were significantly different in distinguishing between mild and severe dysfunction, in which items with r>0. 8 could effectively distinguish KOA patients with high and low score functions, including d420 moving oneself, d465 using equipment for moving around, d510 washing oneself, d640 doing housework, and d470 using transportation.ConclusionICF-RS has a good reliability, validity and criterion-related validity, and can be used to assess the functional status of KOA patients.